Wood grain polypropylene composite material as well as preparation method and application thereof
Through the combination of high -liquidity polypropylene and Mao metamin low -genus and low -primary regulatory polypropylene, and the use of Malay acidic anhydronic polypropylene and dioma silicon oil, it solves the intensity, impact performance and processability of wood grain polypropylene materials. The limitations of aspects realize high luster and good mechanical properties.
Patent Information
- Application Number
- CN202411437051.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-10-15
AI Technical Summary
Woodgrain polypropylene composites have limitations in strength, impact properties and processability, including low mechanical properties, poor interfacial adhesion and difficulty in preparing smooth and glossy parts.
By using high liquidity polypropylene and Mao metamin low -backed polypropylene, combined with Malay acidic anhydride and dioma silicon oil, the method of preparation of the double screw extrusion mechanism is used to improve the compatibility and gloss of the material Spend.
The high luster and good mechanical properties of the wood grain polypropylene composite material are realized, and the processing of the material and the smoothness of the surface are improved.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a wood-grain polypropylene composite material and a preparation method and application thereof. Background Art
[0002] Wood grain polypropylene has a wide range of applications. The following are some common applications: widely used in the construction field, such as making furniture, tables and chairs, integrated cabinets, wardrobes, bookcases, air-conditioning racks, wood-plastic interior doors, floors, exterior wall panels, balcony guardrails, window frames, railings, etc.; in the packaging field, such as packaging pallets, beverage boxes and other various transport turnover boxes; in the industrial field, it can be used as wear-resistant sheds, casting models, machine covers, water pump shells, electrical appliances, etc. in chemical and public places; in the vehicle and ship field, auto parts, auto interior decoration, ship interior decoration, sampans, etc.
[0003] However, wood grain polypropylene also has the following difficult-to-overcome defects:
[0004] 1. Strength and impact performance are limited: The bonding force between hydrophilic wood powder and hydrophobic plastic is small, resulting in lower mechanical strength of the product, lower tensile strength and bending strength than when not filled with plastic, greater brittleness than when not filled with plastic, and correspondingly lower impact strength. In addition, its density is usually higher than that of pure plastic and wood. In order to improve these performance defects, coupling agents can be added to the formula to modify the surface of wood powder, but impact resistance and ductility, brittleness and density may not be significantly improved.
[0005] 2. Processing issues:
[0006] Poor interfacial adhesion: The strong polarity and water absorption of wood powder and the non-polarity and hydrophobicity of most thermoplastics lead to poor compatibility between the two and low interfacial adhesion. When the amount of wood powder filling is large, the fluidity and processability of the material deteriorate, and the difficulty of mixing and extrusion molding increases, which affects the composite performance of wood-plastics. The wood powder needs to be modified to improve the composite performance.
[0007] Since wood powder has a fluffy structure and is easily carbonized at temperatures above 170°C, it is difficult to prepare wood-grain polypropylene parts with a smooth surface and high gloss. Summary of the invention
[0008] The purpose of the present invention is to overcome the above technical defects and provide a polypropylene composite material with wood grain, high surface gloss and good mechanical properties, and a preparation method and application thereof.
[0009] The present invention is achieved through the following technical solutions:
[0010] A wood-grain polypropylene composite material comprises the following components in parts by weight:
[0011] 45 parts of high-flow polypropylene;
[0012]
[0013] In the wood-grain polypropylene composite material of the present invention, the high-fluidity polypropylene resin accounts for more than 40wt% of the total weight percentage of the wood-grain polypropylene composite material.
[0014] The high-fluidity polypropylene has a melt flow rate of 20-50 g / 10 min (test conditions: 230° C. / 2.16 kg) measured according to ISO 1133-1:2022, and an isotacticity of 94-96%.
[0015] The isotacticity of the metallocene low-isotactic polypropylene is 55-65%.
[0016] Preferably, the isotacticity of the metallocene low-isotactic polypropylene is 62-64%.
[0017] The test method for polypropylene isotacticity mainly uses infrared spectroscopy: by analyzing polypropylene in the infrared band 998cm -1 and 973cm -1 The isotacticity is determined by the ratio of the absorbances at
[0018] The particle size of the wood powder is 70-400 meshes.
[0019] The present invention has no limitation on the type of wood powder. For example, pine wood powder with a brand number of WH-100 and a particle size of 100-200 meshes can be selected.
[0020] In the maleic anhydride grafted polypropylene, the grafting rate of maleic anhydride is 1-10wt%, preferably 3-5wt%, wherein the polypropylene as the main chain can be homopolypropylene, the brand is: PP HP500N, Shell Petrochemical Co., Ltd., the melt flow rate is 12g / 10min (test conditions: 230℃ / 2.16kg), and the isotacticity is 97%.
[0021] In the wood-grain polypropylene composite material of the present invention, the maleic anhydride grafted polypropylene can be a commercially available product or can be obtained by self-production, and the self-production method is as follows: according to the weight content of maleic anhydride, maleic anhydride is heated and then injected into a twin-screw extruder containing melted polypropylene through an oil pump, and the result is obtained by reaction extrusion. The test method of maleic anhydride grafting is: acid-base neutralization titration method, which utilizes the property of maleic anhydride reacting with alkali, and calculates the grafting rate of maleic anhydride by titrating the amount of alkali consumed.
[0022] The dimethyl silicone oil in the wood grain polypropylene composite material of the present invention is polydimethylsiloxane, and there is no restriction on the brand of the product. Common brands include Japan Shin-Etsu KF-96-350CS, Wacker AK-350 and the like.
[0023] The amide lubricant is selected from at least one of ethylene bis fatty acid amide lubricants, erucamide lubricants, oleamide lubricants, and hydroxy-modified ethylene bisstearamide; the ethylene bis fatty acid amide lubricant is selected from at least one of ethylene bis fatty acid amide and ethylene bisstearamide; preferably, the amide lubricant is selected from hydroxy-modified ethylene bisstearamide.
[0024] The hydroxy-modified ethylene bisstearamide is obtained by adding hydroxyl groups to ethylene bisstearamide.
[0025] You can choose whether to add 0-2 parts of antioxidant according to the actual situation;
[0026] The antioxidant may be: 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene; 2,5-di-tert-butyl-4-hydroxybenzyl dimethylamine; diethyl-3,5-di-tert-butyl-4-hydroxybenzyl phosphate; stearyl-3,5-di-tert-butyl-4-hydroxybenzyl phosphate; 3,5-di-tert-butyl-4-hydroxyphenyl-3,5-distearyl-thiotriazolylamine; 2,6-di-tert-butyl-4-hydroxymethylphenol; 2,4-di-(n-octylthio)-6-(4-hydroxy-3,5-di-tert-butylglycerol allyl ether)-1,3,5-triazine; N,N'-hexamethylenebis( 3,5-di-tert-butyl-4-hydroxy-hydrocinnamic acid); N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine; octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate; pentaerythritol-tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]; triethylene glycol-bis[3-(3,5-dimethyl-4-hydroxyphenyl)propionate]; triethylene glycol bis[β-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate]; 2,2'-thiodiethyl-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, etc.
[0027] By weight, 0-30 parts of glass fiber are also included.
[0028] The preparation method of the wood grain polypropylene composite material of the present invention comprises the following steps: uniformly mixing the components according to the proportion, extruding and granulating the components through a twin-screw extruder to obtain the wood grain polypropylene composite material. The barrel temperature is set at 180-210° C. and the rotation speed is 350-450 rpm.
[0029] The wood-grain polypropylene composite material of the invention is used for preparing wood-grain products.
[0030] The present invention has the following beneficial effects:
[0031] The beneficial effect of the present invention is that the present invention provides a wood-grain polypropylene composite material, which can obtain a high-gloss resin by compounding high-fluidity polypropylene with metallocene low-isotactic polypropylene, and at the same time, the compounded polypropylene resin has better compatibility with wood powder / maleic anhydride grafted polypropylene, and under the joint action of ethylene bis fatty acid amide and dimethyl silicone oil, a wood powder polypropylene with a smooth surface can be obtained. DETAILED DESCRIPTION
[0032] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0033] The sources of raw materials used in the present invention are as follows:
[0034] Polypropylene A: high fluidity polypropylene, melt flow rate of 30 g / 10 min (test conditions: 230° C. / 2.16 kg), brand PP 320 powder, Hunan Baling Petrochemical, isotacticity of 95%.
[0035] Polypropylene B: metallocene low isotactic polypropylene, isotacticity is 60%, brand is L-MODU S400;
[0036] Polypropylene C: metallocene low isotactic polypropylene, isotacticity is 63%, brand name; PPT500;
[0037] Polypropylene D: ordinary low isotactic polypropylene, isotacticity is 68%, brand name; PP C5608M;
[0038] Polypropylene E: Metallocene isotactic polypropylene, isotacticity is 96%, brand: Purell HM671T;
[0039] Polypropylene F: Metallocene high isotactic polypropylene, isotacticity is 99%, brand name: Achieve1605;
[0040] Polypropylene G: ordinary fluidity polypropylene, CNOOC Shell Petrochemical Co., Ltd., melt flow rate is 12 g / 10 min (test condition: 230° C. / 2.16 kg), brand: PP HP500N; isotacticity is 97%.
[0041] Wood powder: pine wood powder, particle size 150 mesh, from Mujiang Weihua Spice Factory, Shuangshui Town, Xinhui District, Jiangmen City, brand: WH-100;
[0042] Maleic anhydride grafted polypropylene A: mass grafting rate is 1.2wt%, homemade;
[0043] Maleic anhydride grafted polypropylene B: mass grafting rate is 3wt%, homemade;
[0044] Maleic anhydride grafted polypropylene C: mass grafting rate is 5wt%, homemade;
[0045] Maleic anhydride grafted polypropylene D: mass grafting rate 10wt%, homemade;
[0046] Maleic anhydride grafted polypropylene E: mass grafting rate 0.5wt%, homemade;
[0047] Maleic anhydride grafted polypropylene F: mass grafting rate is 12wt%, homemade;
[0048] The self-made method of maleic anhydride grafted polypropylene is as follows: according to the weight content of maleic anhydride, maleic anhydride is heated and then injected into a twin-screw extruder containing melted polypropylene through an oil pump, and then extruded by reaction. The polypropylene is homopolymer polypropylene, brand: PP HP500N, Shell Petrochemical Co., Ltd.
[0049] Maleic anhydride grafted polypropylene G: mass grafting rate 1.2wt%, AD-105, Foshan Bochen Polymer New Materials Co., Ltd.;
[0050] Modified ethylene bis fatty acid amide: TAF, hydroxyl modified ethylene bis stearamide, Guangzhou Yuanya Chemical Co., Ltd.;
[0051] Ethylene bisstearamide: EBS, Guangzhou Runfeng Chemical Co., Ltd.;
[0052] Erucic acid amide: WK1890, Jiangxi Weike Oil Chemical Co., Ltd.;
[0053] Oleic acid amide: WK1618, Jiangxi Weike Oil Chemical Co., Ltd.;
[0054] Other lubricants A: ester lubricant, DP310, Lubrizol;
[0055] Other lubricants B: paraffin lubricant, LOXIOL 2050, Emery;
[0056] Other lubricants C: olefin lubricants, 617A, Honeywell;
[0057] Other lubricants D: fatty acid lubricants, ZINC STEARATE (BS-2818), BELIKE;
[0058] Dimethyl silicone oil: KF-96-350CS, Guangzhou Huigui Composite Materials Co., Ltd., viscosity: 1800mPa.s;
[0059] Vinyl silicone oil: TCP-8008, Guangzhou Tianci Silicone Technology Co., Ltd., viscosity: 1500mPa.s;
[0060] Antioxidants: SONOX 1010, SONOX 168, Sanfeng Chemical Co., Ltd., Linyi City, Shandong Province.
[0061] Embodiment and comparative example Preparation method of wood grain polypropylene composite material: according to the ratio, each component is mixed evenly, and extruded and granulated by a twin-screw extruder to obtain a wood grain polypropylene composite material. The barrel temperature is set to 180-210°C, and the rotation speed is 350-450rpm.
[0062] Preparation method of the board used for glossiness and surface texture: The particles obtained from the twin-screw extruder are passed through a conventional injection molding machine and a 100×100×2.0 mm square board is manufactured through a special mold.
[0063] Various test methods:
[0064] (1) Glossiness: Use a gloss meter to test the glossiness of the square plate at an angle of 60°.
[0065] (2) Surface texture: The roughness comparison sample method is used to evaluate the surface texture of the square plate. The grades are as follows: excellent, good, medium and poor. Good and above can meet the requirements. Among them, "excellent": the surface texture is extremely uniform and fine, with almost no unevenness or roughness visible to the naked eye; "good": the surface texture is relatively uniform, and only a few tiny unevenness can be found upon careful observation, and the overall smoothness is good; "medium": the surface texture has a certain degree of unevenness, and the unevenness can be easily observed, and the smoothness is average; "poor": the surface texture is rough and uneven, and large fluctuations can be clearly seen by the naked eye.
[0066] (3) Tensile strength: tested according to ISO 527-2:2012 standard;
[0067] (4) Notched impact strength: tested in accordance with ISO 180:2023 standard.
[0068] Table 1: Contents of components (parts by weight) and test results of wood grain polypropylene composite materials of Examples 1-7
[0069]
[0070]
[0071] It can be seen from Examples 1 / 5 / 6 / 7 / 8 that the weight content of maleic anhydride in the maleic anhydride grafted polypropylene is preferably 3-5wt%.
[0072] It can be seen from Examples 1 / 4 that the isotacticity of the metallocene low-isotactic polypropylene is preferably 62-64%.
[0073] Table 2: Content of each component (parts by weight) and test results of wood grain polypropylene composite materials of Examples 8-11
[0074]
[0075]
[0076] It can be seen from Examples 1 / 8 that the commercially available maleic anhydride grafted polypropylene product has a similar effect to the homemade raw material technology of the present invention.
[0077] It can be seen from Examples 1 / 9-11 that the glossiness is higher and the mechanical properties are better when the modified ethylene bis fatty acid amide is preferred.
[0078] Table 3: Content of each component (parts by weight) and test results of wood grain polypropylene composite materials of comparative examples 1-6
[0079]
[0080] It can be seen from Example 2 and Comparative Examples 1 / 2 / 3 that ordinary low-isotactic polypropylene, metallocene medium-isotactic polypropylene, and metallocene high-isotactic polypropylene cannot be used to replace metallocene low-isotactic polypropylene. The main reason is that the lower the isotacticity of the polypropylene, the lower the isotacticity of the polypropylene will float on the surface of the square plate when the material is finally made into a square plate by an injection molding machine, thereby improving the gloss and surface texture.
[0081] It can be seen from Example 2 and Comparative Example 4 that it is difficult to fully disperse the wood powder when ordinary fluidity polypropylene is used instead of high fluidity polypropylene.
[0082] It can be seen from Examples 1 / 5 / 6 / 7 / 8 and Comparative Examples 5 / 6 that when the grafting rate of maleic anhydride in maleic anhydride grafted polypropylene is not within the range of 1-10wt% of the present invention, the wood powder cannot be effectively dispersed and cannot form a good bonding force with the resin, and the gloss and surface texture of the obtained material deteriorate.
[0083] Table 4: Content of each component (parts by weight) and test results of wood grain polypropylene composite materials of comparative examples 7-12
[0084]
[0085] It can be seen from Comparative Example 7 that the purpose of the present invention cannot be achieved by using vinyl silicone oil.
[0086] It can be seen from Comparative Example 8 that the dispersibility of wood powder is poor when ethylenebisfatty acid amide is not contained.
[0087] It can be seen from Comparative Example 9 that the bonding strength between wood powder and resin matrix is poor when polypropylene before maleic anhydride grafting is used. That is, when the composite material does not contain maleic anhydride grafted polypropylene with a specific grafting rate, the bonding strength between wood powder and resin matrix becomes poor, resulting in a significant deterioration in the application performance of the polypropylene composite material.
[0088] It can be seen from Comparative Example 10 that when the content of maleic anhydride grafted polypropylene is too high, the mechanical properties will be reduced.
[0089] It can be seen from Comparative Example 11 that when the content of metallocene low-isotactic polypropylene is too low, the dispersibility of wood powder is poor, which not only reduces the gloss and texture, but also reduces the mechanical properties.
[0090] It can be seen from Comparative Example 12 that when the content of metallocene low-isotactic polypropylene is too high, its own tensile strength is low, and when the content is high, the overall tensile strength is lowered and the mechanical properties are poor.
[0091] Table 5: Content of each component (parts by weight) and test results of wood grain polypropylene composite materials of comparative examples 13-16
[0092]
[0093] It can be seen from Comparative Examples 13-16 that other types of lubricants have insufficient dispersion effect on wood powder, resulting in poor application performance of the polypropylene composite material and failure to meet application requirements.
Claims
1. A wood grain polypropylene composite material, characterized in that: By weight, it includes the following components: 45 parts of high-flow polypropylene; 5-15 parts of metallocene low-isotactic polypropylene; 10-50 parts of wood flour; Maleic anhydride grafted polypropylene 0.5-5 parts; 0.5-2 parts of amide lubricant; 0.5-1.5 parts of dimethyl silicone oil.
2. The wood grain polypropylene composite material according to claim 1, characterized in that: The high-fluidity polypropylene has a melt flow rate of 20-50 g / 10 min as measured according to ISO 1133-1:2022, and the test conditions are 230° C. / 2.16 kg.
3. The wood grain polypropylene composite material according to claim 1, characterized in that: The isotacticity of the metallocene low-isotactic polypropylene is 55-65%.
4. The wood grain polypropylene composite material according to claim 3, characterized in that: The isotacticity of the metallocene low-isotactic polypropylene is 62-64%.
5. The wood grain polypropylene composite material according to claim 1, characterized in that: The particle size of the wood powder is 70-400 meshes.
6. The wood grain polypropylene composite material according to claim 1, characterized in that: In the maleic anhydride grafted polypropylene, the grafting rate of maleic anhydride is 1-10wt%, preferably 3-5wt%.
7. The wood grain polypropylene composite material according to claim 1, characterized in that: The amide lubricant is selected from at least one of ethylene bis fatty acid amide lubricants, erucamide lubricants, oleamide lubricants, and hydroxy-modified ethylene bisstearamide; the ethylene bis fatty acid amide lubricant is selected from at least one of ethylene bis fatty acid amide and ethylene bisstearamide; preferably, the amide lubricant is selected from hydroxy-modified ethylene bisstearamide.
8. The wood grain polypropylene composite material according to claim 1, characterized in that: By weight, it also includes 0-2 parts of antioxidants; by weight, it also includes 0-30 parts of glass fibers.
9. The method for preparing the wood-grain polypropylene composite material according to any one of claims 1 to 8, characterized in that: The components are uniformly mixed according to the proportion, and extruded and granulated by a twin-screw extruder to obtain a wood-grain polypropylene composite material.
10. Use of the wood grain polypropylene composite material according to any one of claims 1 to 8, characterized in that: Used to prepare wood grain products.
Citation Information
Patent Citations
Polypropylene plastic-wood composite material and preparation method thereof
CN110964286A
Glass fiber reinforced polypropylene composition as well as preparation method and application thereof
CN112521686A
High-gloss wear-resistant flame-retardant polypropylene composite material and preparation method thereof
CN112646268A
Polypropylene composite material as well as preparation method and application thereof
CN113912949A
Polypropylene calcium carbonate master batch as well as preparation method and application thereof
CN114163721A